Manufacturing a low-cost ceramic water filter and filter system for the elimination of common pathogenic bacteria - Simonis, J.J.; Basson, A.K. (Physics and chemistry of the earth. Parts A/B/C, 2012)
► Demonstrate a low-cost method for making ceramic water filters. ► Illustrate a novel water filtration system that is both fast and effective. ► Prove the filter effectiveness against micro-organisms in water. Africa is one of the most water-scarce continents in the world but it is the lack of potable water which results in diarrhoea being the leading cause of death amongst children under the age of five in Africa (696 million children under 5years old in Africa contract diarrhoea resulting in 2000 deaths per day: WHO and UNICEF, 2009). Most potable water treatment methods use bulk water treatment not suitable or available to the majority of rural poor in Sub-Saharan Africa. One simple but effective way of making sure that water is of good quality is by purifying it by means of a household ceramic water filter. The making and supply of water filters suitable for the removal of suspended solids, pathogenic bacteria and other toxins from drinking water is therefore critical. A micro-porous ceramic water filter with micron-sized pores was developed using the traditional slip casting process. This locally produced filter has the advantage of making use of less raw materials, cost, labour, energy and expertise and being more effective and efficient than other low cost produced filters. The filter is fitted with a silicone tube inserted into a collapsible bag that acts as container and protection for the filter. Enhanced flow is obtained through this filter system. The product was tested using water inoculated with high concentrations of different bacterial cultures as well as with locally polluted stream water. The filter is highly effective (log10>4 with 99.99% reduction efficiency) in providing protection from bacteria and suspended solids found in natural water. With correct cleaning and basic maintenance this filter technology can effectively provide drinking water to rural families affected by polluted surface water sources. This is an African solution for the more than 340 million people in Africa without access to clean drinking water (WHO and UNICEF, 2008).